Pengaruh Promosi Media Sosial Terhadap Minat Beli Penjualan Produk Sweetpuding.Plp - Rafiqah Asaff; Dewi Hardiiyanti Sahabuddin; Natasya Florin; Nabila Putri; Aidil Fitrawan (STIM-LPI Makassar, 2026)
This study aims to analyze the effect of social media promotion on consumers' purchase intention toward Sweetpuding.PLP products in Palopo City. The research employed a quantitative causal-associative approach with a sample of 70 respondents selected using incidental sampling. Primary data were collected through questionnaires and analyzed using validity testing, reliability testing, classical assumption testing, simple linear regression analysis, t-test, and the coefficient of determination (R²), with the assistance of SPSS. The results showed that social media promotion does not have a significant effect on consumers' purchase intention, with a regression coefficient of -0.104, a t-value of 0.830, and a significance value of 0.409 (>0.05). The coefficient of determination (R Square) of 0.010 indicates that social media promotion explains only 1.0% of the variation in consumers' purchase intention, while the remaining 99.0% is explained by other factors outside the research model. This study concludes that social media promotion has not been able to significantly influence consumers' purchase intention toward Sweetpuding.PLP products. Therefore, business owners are advised not to rely solely on social media promotion but also to improve product quality, offer competitive prices, and build consumer trust to increase purchase intention more effectively.